A literatura de genocídio: ’raconter l’indicible’ - Rodrigues Florêncio, Jéssica; Pinheiro-Mariz, Josilene (Revista Leitura, 2019)
Este artigo tem como foco a literatura de genocídio – em especial, o acontecido em Ruanda – como nova forma de escrita que pode perpassar os campos literário e histórico, bem como fomentar a sensibilização à leitura literária e o pensamento crítico do estudante de língua estrangeira. Dessa forma, fornecemos dois exemplos de livros que fazem parte dessa nova forma de escrita. Para tanto, nossas reflexões se baseiam em Ferreira (2010), Foster (2011) e Nora (1993) acerca da literatura, memória e história; bem como nas discussões de Chevrier (2006), Coquio (2004, 2015) e Germanotta (2010), quanto à literatura de genocídio. Assim, percebemos que a literatura de genocídio tem como objetivo a resistência ao esquecimento e à repetição da prática testemunhada. É por se tratar dessa resistência e da relação entre o ético e o estético, que essa escrita se torna quase impossível de ser produzida: é, de fato, raconter l’indicible. The literature of genocide: raconter l’indicible This article focuses on the literature of genocide – especially the one that happened in Rwanda – as a new way of writing that can pass through the literary and the historical fields, as well as to raise awareness about literary reading and to foster the critical thinking of the foreign language student. Thus, we provide two examples of books that are part of this new way of writing. For this purpose, our reflections are based on Ferreira (2010), Foster (2011) and Nora (1993), regarding literature, memory and history; and based on Chevrier’s (2006), Coquio’s (2004, 2015) and Germanotta’s (2010) discussions about literature of genocide. So we understand that the aim of the literature of genocide is the resist to forgetfulness and repetition of the witnessed practice. Due to this resistance and the relationship between the ethical and the aesthetical, this writing becomes almost impossible to be produced: it is, indeed, raconter l’indicible. Keywords: Francophone literature. Literature of genocide. Literature and History. Reader development DOI: 10.28998/2317-9945.2019n63p275-291